Cognitive Stimulation and Psychopedagogy: Intersection of Approaches for Improving the Quality of Life of Older Adults (Revista Electrónica Calidad en la Educación Superior, 2025)
This study analyzes how psychopedagogical strategies in cognitive stimulation programs can strengthen the cognitive skills and emotional well-being of older adults in Costa Rica. Through a qualitative approach, the experiences and perceptions of the participants in a Cognitive Stimulation Manual and Workshop were explored, identifying improvements in memory, attention and socialization. The findings highlight the importance of active and collaborative methodologies in the learning of this population. It is recommended to expand these programs to various educational and community contexts, ensuring their accessibility and sustainability through interdisciplinary approaches.
Keywords: psychopedagogical strategies; cognitive stimulation; older adults; emotional well-being; active learning